2019
DOI: 10.12707/riv18069
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of victims of traumatic brain injuries undergoing neurosurgery

Abstract: Qualidade de vida das vítimas de trauma cranioencefálico submetidas a neurocirurgias Calidad de vida de las víctimas de traumatismo craneoencefálico sometidas a neurocirugías

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…In addition, these ndings concour with a study that reported that surival of TBI patients was low and elavated blood pressure, GSC, and non reactive pupils are predictors of mortality (12). Holding the rest of variables constant, given a patient has EIH, having SDH, SAH and contusion (Figures would make the overall survival become worse over time (33)(34)(35)(36). Patients with EIH after TBI had a 30-fold higher risk of adverse outcomes and a 10-fold higher chance of dying (37).…”
Section: Factors Associated With Survivalsupporting
confidence: 64%
“…In addition, these ndings concour with a study that reported that surival of TBI patients was low and elavated blood pressure, GSC, and non reactive pupils are predictors of mortality (12). Holding the rest of variables constant, given a patient has EIH, having SDH, SAH and contusion (Figures would make the overall survival become worse over time (33)(34)(35)(36). Patients with EIH after TBI had a 30-fold higher risk of adverse outcomes and a 10-fold higher chance of dying (37).…”
Section: Factors Associated With Survivalsupporting
confidence: 64%
“…Decision-making is challenging in the care of these individuals, particularly concerning their prognosis, the actual impact of new interventions, and the real potential to alter their quality of life. In this scenario, Palliative Care (PC) has been one of the most effective and necessary frameworks in therapy for TCE patients (Lima et al, 2019).…”
Section: )mentioning
confidence: 99%
“…Decision-making is challenging in the care of these individuals, particularly concerning their prognosis, the actual impact of new interventions, and the real potential to alter their quality of life. In this context, Palliative Care (PC) has been one of the most effective and necessary frameworks for treating TBI patients [4].…”
Section: Introductionmentioning
confidence: 99%